The Relationship Between Knowledge And Readiness For Menarche In Class V Students At Sd N 01 Kaur District - Saputra, Yuda Agung; Fauzi, Yusran; Retni, Retni (Universitas Dehasen Bengkulu, 2022)
Menarche or first menstruation is a sign that a girl is entering puberty/adolescence. Young women need information and knowledge about the menstrual process and health during menstruation. Young women will experience difficulties in dealing with menstruation for the first time if they have never previously obtained an overview of knowledge about menstruation. The purpose of this study was to find out the relationship between knowledge and readiness in facing menarche in fifth grade students at SD N 01 Kaur District. The method used was an analytic survey research with a cross-sectional research design. The data was collected in the form of primary data by distributing questionnaires to 32 fifth grade students at SD N 01 Kaur Regency using total sampling technique. Data analysis was performed using the Chi-Square test. The results of the univariate analysis showed that almost half of the students, namely 15 (46.9%), had less knowledge and most of the students, namely 17 (53.1%), were not ready to face menarche. The results of the bivariate analysis showed that there was a relationship between knowledge and readiness to face menarche in fifth grade students where the value of p = 0.012. The researcher suggests that the school be able to provide direction and information to students so that their knowledge about menarche is good.